ANALISIS PENGARUH INVESTASI, UPAH, DAN PERTUMBUHAN EKONOMI TERHADAP PENGANGGURAN TERDIDIK LULUSAN PERGURUAN TINGGI DI INDONESIA - Arisusanti, Luh Made; Gde Bendesa, I Komang (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 12 No 6 (2023): Vol.12.6.JUNI.2023[376-450]DO - 10.24843/EEP.2023.v12.i06.p02, 2023)
ABSTRACT ABSTRACT Unemployment is still the main problem of the Indonesian economy. The number of unemployed people in Indonesia is mostly from young people or productive young population and most of them are educated or often called educated unemployed. The purpose of the study is to analyse the effect of investment, provincial minimum wage, and economic growth simultaneously and partially on the unemployment rate of educated university graduates in Indonesia. This research was conducted in 34 provinces of Indonesia from 2010-2021 with 408 total observations. This study uses panel data and the model selected in this study is Fixed Effect Model (FEM). The results showed that partially, investment had a positive and insignificant effect, the Provincial Minimum Wage had a positive and significant effect, and economic growth had a negative and significant effect on the educated unemployment rate of university graduates in Indonesia. keyword : Investment, Provincial Minimum Wage, Economic Growth, Educated Unemployment